KEEFEKTIFAN PENDEKATAN PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) BERBANTU PERMAINAN TRADISIONAL DHAKON TERHADAP KEMAMPUAN BERHITUNG PERKALIAN SISWA KELAS II - Tri Puspita Rini, Mei Fita Asri Untari, (MALIH PEDDAS, 2013)
Goals to be achieved in this study are (1) knowing or mastery learning achievement of students with learning PMRI approach by traditional game âDhakonâ, (2) knowing the differences of studentâs calculation capibility of multiplication between learning use PMRI approach by traditional game âDhakonâ with conventional learning. This research is quantitative. The population of this research are students in SD Negeri Gayamsari 01 Semarang second grade. The sample in this research population were all taken by the students of class II A and II B SD Negeri Gayamsari 01 Semarang. The independent variable in this research is learning PMRI approach by traditional game âDhakonâ, and the dependent variable is the multiplication numeracy skills. The method of data collection using interviews, documentation, testing and observation. For data analysis mastery learning one sample t test was used to measure numeracy and multiplication use two-sample t test. Based on the results of the study showed an average multiplication numeracy of experimental group 90,75 and the control group 80. Based on the homogeneity test obtained Fhitung 1,77 and with Î± 5%, Ftabel 2,168 thus obtained Fhitung <Ftabel, meaning both homogeneous group. Based on a sample t-test in the experimental group gained thitung = 14,41 with Î± = 5% and df = 19 obtained Ttabel = 1,729. Because thitung> ttabel then H0 rejected so it can be concluded that the multiplication numeracy skills of students in the experimental group on average 65. Based on two-sample t test obtained thitung = 3,61 and with Î± 5% was obtained Ttabel = 2,0244. Because thitung> ttabel then H0 is rejected and Ha accepted, thus there is a difference in average numeracy skills that students multiplication numeracy experimental group is better than control group multiplication numeracy. Suggestions researchers, learning PMRI approaches should be developed to another subject that students have a picture of the material being studied relations with its application in everyday life.